ANALISIS TEKNO-EKONOMI KINERJA PEMBANGKIT LISTRIK TENAGA SURYA UNTUK FASILITAS PUBLIK DI KAWASAN WISATA PUNCAK LABUANG - Pribadi, Rizki Aditio; Fitriadi, Fitriadi; Asrul, Junaidi; Firmansyah, Firmansyah; Herisajani, Herisajani; Yuhaidizen, Yuhaidizen (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2025)
This article discusses the performance analysis of solar power plants for public facilities reviewed from a techno-economic perspective using the Homer application. The research location in this article is the public facility of Surau Nur Jannah in the Puncak Labuang Limau Manis Tourism Area, Padang City. Based on field visits, the community conveyed the limited resources related to the development of the tourism area, one of which is the availability of electrical energy. Based on the problems conveyed by the community, Padang State Polytechnic through the Department of Electrical Engineering provides a solution to the problem of limited electrical energy sources, by offering the concept of Renewable Energy. The initial stage of providing electrical energy sources is to build an Off-Grid Solar Power Plant with a capacity of 240 WP. In order to support the construction of the Solar Power Plant at the specified location, it is necessary to conduct a performance and economic analysis of the development. This location has a fairly large potential for solar resources, on average in one year this place receives solar radiation of 4.91 kWh/m3/Day. The most optimal configuration from the simulation results is a combined system, two units of 1 kW Generic Photovoltaic, Converter, Storage / Battery. The production of electrical energy with this configuration obtains 39.6 kWh/year of electricity with a total consumption in one year of 29.2 kWh/year. The results of the analysis of the power plant's performance from a techno-economic aspect provide positive results, with a Cost Of Energy (COE) of Rp. 1,095.34/kWh. This article aims to provide an understanding of the construction of small-scale power plants for public facilities with minimum costs